Markerless motion capture system based on webcams using OpenPose - Lim, W. (International Journal of Human Movement and Sports Sciences, 2022)
Recently, webcam-based motion capture systems have attracted tremendous attention as alternative low-cost motion analysis tools, owing to the rapid advancement of markerless technologies. Although the upper and lower limbs are moved simultaneously in most function activities in daily life, most existing studies focused on kinematic data observed in the hip and knee joints during gait. The purpose of this study was to measure the kinematic data of the upper and lower limb simultaneously during modified squat, using low-cost webcams and to compare them to those of the 3D marker-based motion capture system. The modified squat was performed nine times in total without rest in between. The modified squat consisted of hip and knee flexion with elbow flexion. During modified squat, the kinematic data were collected using 4 RGB cameras and 13 Vicon cameras. The positions of the joints were obtained using OpenPose and the 3D positions were reconstructed using OpenCV. Angular trajectories from the Vicon motion capture system tended to be very similar to the ones from the webcam-based motion capture system. There was no significant difference in the kinematic data at the elbow between two different capture systems. Additionally, the minimum joint angles at the hip and knee were not significantly different. It was confirmed that the markerless motion capture system based on webcam can measure angular joint motions at the same level as the Vicon 3D motion capture system with markers. The webcam-based motion capture system will enhance the usability in clinical settings.